Impact of potassium management on soil dynamics and crop uptake in rice systems - Mohapatra, Suchismita; Rout, Kumbha Karna; Khanda, Chandramani; Mishra, Amit; Yadav, Sudhir; Padbhushan, Rajeev; Mishra, Ajay Kumar; Sharma, Sheetal (Frontiers Media, 2025)
Rice, a staple crop in Asia, is critical for the region’s food security. However, intensive rice farming has led to substantial potassium (K) depletion in soils, undermining soil fertility and crop productivity. This study assessed the impact of different K management strategies on soil K dynamics, balance, and crop uptake in a puddled, transplanted rice–rice system in Odisha, India, during dry (December–April) and wet (June–October) seasons. The experiment involved nine treatments, including combinations of chemical fertilizers, straw application, and foliar spray, arranged in a randomized block design (RBD). Grain yield was significantly higher when applying chemical fertilizer and foliar spray (3.9 t ha−1 in the dry season and 5.4 t ha−1 in the wet season) compared to the control (2.7 and 4.2 t ha−1, respectively). Higher levels of exchangeable and reserve K were retained with chemical fertilizer applications, while reduced fertilizer doses combined with straw utilized more non-exchangeable K. The dry season exhibited a greater shift in non-exchangeable K, indicative of larger soil K depletion. Treatments combining reduced fertilizer doses with straw yielded a positive K balance, in contrast to the negative balance observed with chemical fertilizers alone. Correlation analyses indicated that reserve and non-exchangeable K significantly contributed to maintaining available K levels in the soil solution, thereby supporting continuous crop K uptake. These findings highlight the necessity of integrating reserve and non-exchangeable K dynamics into nutrient management strategies to ensure sustainable rice production.